Atypical infantile genital Molluscum contagiosum - Kaiwen Zhuang; Yuping Ran; Fengni Xu; Jebina Lama (Sociedade Brasileira de Dermatologia, 2015)
Abstract Genital molluscum contagiosum is rare in children. We report a molluscum contagiosum around the vulva and anus of 9-year-old girl, which has atypical presentations and was finally confirmed by histopathological and electron microscopy findings.